Gain with no pain? Pain management in dermatological photodynamic therapy. (31st July 2017) - Wang, B.; Shi, L.; Zhang, Y.F.; Zhou, Q.; Zheng, J.; Szeimies, R.M.; Wang, X.L.
Summary: Pain during photodynamic therapy (PDT) is the main limiting adverse effect in its use in dermatology. Given its multifactorial nature, we reviewed both intrinsic and extrinsic factors that are involved in PDT pain. We propose a threshold theory for pain experience in PDT: it correlates positively with fluence rate and dose below a certain threshold (rate of ~60 mW cm −2, dose of ~50 J cm −2 ); when the threshold is surpassed, pain intensity saturates. Additionally, we carefully compared recent updates on pain management strategies and we suggest that cold‐air analgesia and low‐irradiance light sources (such as variable pulsed light and daylight PDT) represent the current best analgesic options. Finally, we discuss the possible mechanisms of pain experience during PDT. Reactive oxygen species, transient receptor potential channels and inflammatory responses are key mediators in pain. Further investigation into these pathways should help with the development of more effective analgesic strategies. Taking these points together, for pain management in PDT, an individualized plan of analgesia is possible. Abstract : What's already known about this topic? Pain is the main adverse effect of photodynamic therapy (PDT). PDT pain is a multifactorial event with many influencing factors. Traditional topical and oral anaesthetics are ineffective in PDT pain management. Several other analgesic measures have been invented and studied. What does this study add? In this review we summarize the influencing factors of pain experience during PDT. We compared each of the pain management strategies in terms of mechanism of action, effectiveness and feasibility. Cold‐air analgesia and low‐irradiance light sources represent the current best analgesic options. We review potential mechanisms of pain during PDT and provide insights into pain management. Plain language summary available online